Bangladesh : Seeking Better Employment Conditions for Better Socioeconomic Outcomes. (Studies on growth with equity., 2013)
This study on Bangladesh, part of the on-going series entitled Studies on Growth with Equity, highlights that many of these migrant workers are often confronted with difficult employment conditions abroad and their remittances have not translated into higher investment - which has further dampened productivity gains and formal job creation at home.